1999
DOI: 10.1063/1.125178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indium doping on the transient optical properties of GaN films

Abstract: We have investigated the effects of In doping on the optical properties of GaN films grown by gas-source molecular-beam epitaxy. Time-resolved photoluminescence was carried out to study the transient optical properties of the epitaxial films. In comparison to the undoped GaN film, the spontaneous emission lifetime was prolonged from below 20 to 70 ps by doping with In. Under high-excitation density, stimulated emission was observed from both samples. The threshold excitation density was found to be reduced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
16
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 13 publications
6
16
1
Order By: Relevance
“…All these improvements are more significant for samples grown with nitrogen as a carrier gas, having higher dislocation density. This is consistent with the previously observed rather drastic improvements of properties for MBE-grown samples, 4,5 where the dislocation density is much higher.…”
Section: ͓S0003-6951͑00͒02723-6͔supporting
confidence: 93%
“…All these improvements are more significant for samples grown with nitrogen as a carrier gas, having higher dislocation density. This is consistent with the previously observed rather drastic improvements of properties for MBE-grown samples, 4,5 where the dislocation density is much higher.…”
Section: ͓S0003-6951͑00͒02723-6͔supporting
confidence: 93%
“…Recently, it was found that isoelectronic In doping has definite effects of controlling the density of dislocations and improving the GaN film quality. Some experimental reports on the characteristics of In-doped GaN films investigated from a viewpoint of optical [6][7][8], electrical [9,10], and growth properties [11] have been published. However, there are few reports about the behavior of deep level defects with isoelectronic In doping.…”
mentioning
confidence: 99%
“…Indium is the most widely studied surfactant in the epitaxial growth of GaN. The improvement in the crystalline quality, electrical and optical properties, and surface morphology of the In-doped GaN have been reported for MOVPE [2][3][4][5] and MBE [6,7]. The roles of the In surfactant in the MOVPE growth of GaN are more significant when the N 2 carrier gas is used in comparison with the H 2 .…”
mentioning
confidence: 99%